Topical analgesic and local anesthetic agents for pain associated with chronic leg ulcers: A systematic review - Anne Purcell, & Thomas Buckley, & Jennie King, & Wendy Moyle and & Andrea P. Marshall & (WCET Journal - Spanish Edition, 2020)
Objective  To examine the evidence related to the effectiveness of topical analgesic and topical local anesthetic agents for reducing pain associated with chronic leg ulcers.  Methods  A systematic search and review of the literature were undertaken using key search terms such as leg ulcers, topical anesthetics, topical analgesics, and pain. Six databases were electronically searched for articles published between January 1990 and August 2019.  Results  A total of 23 articles were identified that met the inclusion criteria. Data were extracted using content analysis. Most of the included studies were randomised controlled trials; however, the reported methodology for most of studies was poor, and so the validity and reliability of the evidence are uncertain. Lidocaine/prilocaine cream, ibuprofen foam, and morphine gel were the most examined topical agents. Lidocaine/prilocaine cream significantly improved wound-related pain compared with all other studied agents. For topical analgesic agents, ibuprofen foam also reduced chronic leg ulcer pain significantly, whereas morphine gel was ineffective. Conclusions  Lidocaine/prilocaine cream and ibuprofen foam are effective agents for reducing wound-related pain associated with chronic leg ulcers. Effective use of topical agents could reduce the need for systemic pain relief agents, mitigating potential adverse effects, while giving clinicians another treatment option to manage wound-related pain associated with chronic leg ulcers.